Comparing the efficacy of monofocal and multicfocal IOLs in phacoemulsification of cataract in eyes with high myopia (Ukrainian Journal of Ophthalmology, 2025)
Background: High myopia is a factor that complicates and may affect the visual outcome of phacoemulsification of cataract. There is no agreement among ophthalmologists as to whether it is appropriate to implant a multifocal intraocular lens (IOL) in high myopia. Such doubts are caused by frequent complications in the fundus which cannot be found before surgery, leading to the impossibility of an accurate postoperative visual prognosis. However, the patient’s desire to improve vision does not allow abandoning the idea of implanting a multifocal lens in eyes with high myopia. Purpose: To compare treatment outcomes among eyes with high myopia which underwent phacoemulsification with implantation of monofocal versus multifocal IOLs.Material and Methods: We reviewed the visual outcomes of 55 patients (93 eyes) with high myopia who had undergone phacoemulsification and IOL implantation. Study eyes were divided into two groups depending on the type of IOL implanted. Group A included 22 patients (38 eyes) with a multifocal IOL implanted. In this group, there were 11 women (55%) and 9 men (45%), and patient age ranged from 29 years to 73 years (mean age, 52 ± 2.9 years). Group B included 32 patients (55 eyes) with a monofocal IOL implanted. In this group, there were 18 women (51.4%) and 16 men (48.6%), and patient aged ranged from 32 years to 78 years (mean age, 58 ± 2.1 years). Preoperatively, patients underwent a routine eye examination which included automated refraction, visual acuity, perimetry, Amsler test, phosphene test, tonometry, biomicroscopy, direct ophthalmoscopy, and, if possible, retinal examination using a Goldmann lens. In addition, they underwent a special examination for the patients being prepared for phaco plus IOL implantation which included ultrasound A- and B-scanning (Alcon; USA), optical biometry (IOL Master 700 - Carl Zeiss Meditec AG, Germany), and endothelial microscopy (SP-3000P, Topcon Corporation, Japan). The Haigis and SRK-T formulas were used for IOL calculation. Results: At one month after phacoemulsification, eyes in both groups showed improved visual acuity. In the eyes of group A, mean uncorrected visual acuity (UCVA) increased by 76% to 0.8 ± 0.03 and mean best-corrected visual acuity (BCVA), by 86% to 0.9±0.02, whereas mean Sph and mean Cyl values were -0.06 ± 0.08 D and -0.59 ± 0.15 D, respectively. In the eyes of group B, UCVA increased by 49% to 0.55 ± 0.02 and mean BCVA, by 78% to 0.84±0.02, whereas mean Sph and mean Cyl values were -0.85 ± 0.11 D and -0.94 ± 0.12 D, respectively. These results maintained for six months, and the difference between values at month 1 and month 6 was not statistically significant (p > 0.05) for all cases. After phacoemulsification and IOL implantation, in the eyes of group A, mean spherical component decreased by 12.88 ± 0.2 D to -0.22±0.11 D, whereas mean cylindrical component decreased by 1.0 ± 0.1 D to -0.8 ± 0.1 D as assessed by autoreftactometry. In addition, at one month, in the eyes of group B, mean spherical component decreased by 12.63 ± 0.12 D to -0.84 ± 0.02 D, and approached a target value, whereas a change in a cylindrical component was not statistically significant. The eyes with an implanted multifocal IOL were found to be well adapted to near work and showed a mean near vision acuity of 0.9 ± 0.1 versus 0.6 ± 0.1 for the eyes with an implanted monofocal IOL. Aberrations were significantly less in group A than in group B.Conclusion: First, among the eyes with high myopia, the percentage increase in uncorrected visual acuity was larger in those with an implanted multifocal IOL (76%) than in those with an implanted monofocal IOL (49%), and the difference was significant (р < 0.05). Second, the increase in near visual acuity was by 33% larger in those with an implanted multifocal IOL than in those with an implanted monofocal IOL, which significantly improved their quality of life, enabling them to quit wearing their glasses. Finally, our findings demonstrate that high myopia is not a contraindication for implanting a multifocal IOL.
Keywords: High myopia; phacoemulsification of cataracts; multifocal IOL; monofocal IOL